A Case of Pregnancy Complicated by the Development of a Tubo-Ovarian Abscess Following an Aspiration of Endometrioma During Oocyte Pick up - Recep Emre Okyay; Ali Cenk Özay; Özlen Emekçi; Ali Rıza Taylan Bodur; Ömer Erbil Doğan (Medical Network, 2016)
A 28 year old nulligravid woman applied to our department at 26 weeks' gestation with a severe abdominal pain. She had a medical history of an endometrioma aspiration during IVF cycle. There was no history of symptomatic pelvic inflammatory disease or abdominal surgery. Her pregnancy was progressing well until 18 weeks gestation, when she started to complain of abdominal pain. When she reached 26 weeks gestation she got fever and her abdominal pain became more severe. The patient was operated urgently. During laparatomy, we observed purulent fluid filling the abdominal cavity and a 10 cm right adnexial mass compatible with tuboovarian abscess. We drained the abscess and excised her cyst with its wall. She was started on intravenous antibiotics-metronidazole and ceftriakson, tocolytic treatment with magnesium sulfate and indometazine. Also betametazone was added to her treatment. The patient delivered vaginally at 38 weeks of gestation. The baby was healthy and weighed 3150 gr.